Analisis Risiko Kesehatan Lingkungan Fasilitas Jamban di Desa Jetis, Kecamatan Nusawungu, Kabupaten Cilacap - Amyati, Amyati; Triyono; Warniningsih (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2025)
This research aims to analyze the condition of latrine facilities and assess environmental health risks in Jetis Village, Nusawungu District, Cilacap Regency. The study is part of the Environmental Health Risk Assessment (EHRA) conducted for the development of the District Sanitation Strategy (SSK). The method employed was a participatory household survey in the selected village, focusing on latrine facility indicators and sanitation behavior based on STBM pillars. The study results indicate that although private latrine access reached 93%, the greatest risk stems from fecal sludge management. A total of 95% of septic tanks were suspected to be unsafe and 67.8% were never emptied, indicating a high potential for contamination. Furthermore, Open Defecation (OD) behavior was still detected in 22.7% of households. These findings highlight the urgency of sanitation interventions focused on improving septic tank safety at the study location.